ANALISIS KETIMPANGAN PEMBANGUNAN WILAYAH DI PROPINSI DAERAH ISTIMEWA YOGYAKARTA - Ary Sutrischastini; Suci Utami Wikaningtyas (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2026)
In regional economic studies, the issue of development inequality between regions is a significant topic of interest, including in the Special Region of Yogyakarta. According to data from the Central Statistics Agency (BPS) in March 2025, the Gini ratio in the Special Region of Yogyakarta was higher than the national average. This indicates a greater income gap in Yogyakarta. The objective of this study was to analyze regional development inequality and identify leading sectors with potential for development in the Special Region of Yogyakarta. The research was conducted in the Special Region of Yogyakarta Province. The data sources were secondary data collected from the BPS for 2020–2024, including per capita GRDP and the population of the Special Region of Yogyakarta (DIY). The analysis tool used was the Williamson Index to measure regional development inequality and the Location Quotient (LQ) to determine leading or base sectors. The results showed that regional development inequality in the Special Region of Yogyakarta Province was categorized as high, with an average Williamson Index value of 0.51658597. Meanwhile, the LQ analysis results showed that Yogyakarta City has ten basic sectors, followed by Gunung Kidul Regency with seven basic sectors, Bantul and Kulon Progo Regencies each with six basic sectors. Meanwhile, Sleman Regency has the fewest leading sectors, with five.